The Strategy of The Community of Latu In Maintaining Its Government Institutions In The West Seram District - Laiuluy, Elisa; Manda, Darman; Syukur, Muhammad (Journal of Scientific Research, Education, and Technology (JSRET), 2023)
This study aims to find out the strategy of the people of Negeri Latu in maintaining their government institutions and to know the structure in government institutions of the people of Negeri Latu. This study's data were evaluated via qualitative descriptive analysis in three stages: data reduction, data presentation, and conclusion drawing. Various data collecting methods include observation, interviews, and documentation.The results of this study indicate that the forms of strategy undertaken by the people of Negeri Latu in maintaining their customary government institutions include: (1) holding demonstrations to the regional government of the western part of Seram Regency, (2) making petitions and letters of refusal to participate in the election of the village head to the local government of the western part of Seram district, (3) carrying out the preservation of traditions or local wisdom to maintain their existence for each generation. In addition, it was found that the existence of the traditional governance system of the Land of Latu still exists today. In addition, according to the results of the research conducted, it can be seen how the Latu government system with its various sub-systems still exists and is still being maintained by the Latu people to this day.